Increase of efficiency of relay protection of autotransformers 750 kV with the longitudinally-transversal adjusting - Yandulskyi, O. S.; Marchenko, A. A.; Zakolodiazhnyi, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The question of insufficient sensitiveness of basic protection at short circuits on earth of regulative input of autotransformers 750 kV with the longitudinally-transversal adjusting is considered. The model of АТ is built and the currents of short circuit and differential current are investigated in different taps positions of longitudinal and transversal regulators.